URINARY TRACT INFECTION IN CHILDREN - T. V. Margieva; O. V. Komarova; I. S. Kostushina; G. T. Yakhyaeva; A. M. Mazo; T. V. Vashurina; O. A. Zrobok (Педиатрическая фармакология)
The issues of diagnosing and treating urinary tract infections and their role in development of renal injury are being actively discussed by scientists and practicing pediatricians. The article presents the most recent data on etiological factors, pathogenesis and clinical manifestations of this disease. It provides recommendations on diagnosis and management of patients depending on their age. The article presents a discussion of antibacterial therapy course duration and indications for anti-relapse treatment. The study demonstrates that intravenous antibacterial therapy must be launched immediately in neonates in the event of pyretic fever; empirical antibacterial therapy must be launched immediately in older children after diagnosis of the urinary tract infection has been confirmed; subsequently, treatment ought to be corrected depending on the results of a bacteriological trial, sensitivity to antibiotics and effectiveness of the prescribed antibiotic. Along with normalization of urination rhythm and water intake schedule, antibacterial preventive therapy might be considered, if effective, in the event of recurrent nature of the urinary tract infection.